2021
DOI: 10.1080/03601234.2021.1885262
|View full text |Cite
|
Sign up to set email alerts
|

How macrophages respond to two-dimensional materials: a critical overview focusing on toxicity

Abstract: With wider use of graphene-based materials and other two-dimensional (2D) materials in various fields, including electronics, composites, biomedicine, etc., 2D materials can trigger undesired effects at cellular, tissue and organ level. Macrophages can be found in many organs. They are one of the most important cells in the immune system and they are relevant in the study of nanomaterials as they phagocytose them. Nanomaterials have multi-faceted effects on phagocytic immune cells like macrophages, showing sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 233 publications
(245 reference statements)
0
12
0
Order By: Relevance
“…summarized the biological effects of TNMs and macrophages to better understand and predict the possible mechanism. [ 163 ] Thongkumkoon et al. found that direct contact between naked DNA and WO 3 nanoplates led to DNA damage and induced mutations that led to cancer, disease, and gene changes.…”
Section: Research Hotspots Of Tnms In the Biomedical Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…summarized the biological effects of TNMs and macrophages to better understand and predict the possible mechanism. [ 163 ] Thongkumkoon et al. found that direct contact between naked DNA and WO 3 nanoplates led to DNA damage and induced mutations that led to cancer, disease, and gene changes.…”
Section: Research Hotspots Of Tnms In the Biomedical Fieldmentioning
confidence: 99%
“…Lin et al summarized the biological effects of TNMs and macrophages to better understand and predict the possible mechanism. [163] Thongkumkoon et al found that direct contact between naked DNA and WO 3 nanoplates led to DNA damage and induced mutations that led to cancer, disease, and gene changes. [164] Song et al attempted to assess toxicity by investigating the interactions between WO 3-x and two ubiquitous protein domains involved in protein-protein interactions.…”
Section: Toxicity Evaluationmentioning
confidence: 99%
“…Mechanistic studies investigating acute toxicity response to various environmental and occupational exposures consisting of spherical, 2D, or high aspect ratio particulates highlight the role of molecular initiating events NF-κB and NLRP3 inflammasome activation. [52][53][54][55][56][57] The influence of impurities and increase in presence of high aspect ratio particulate with increasing BNNT purity was further investigated using a mechanismbased screening approach. This approach evaluated the dose response in activation of these molecular initiating events with hBN, AP-, BR-, W1-, and W2-BNNTs.…”
Section: Mechanism-based Screeningmentioning
confidence: 99%
“…161 The pathogenicity of long, stiff, biopersistent respirable fibers or nanofibers is well established, 162,163 but for non-fibrous 2D materials the causal relationship between shape, size, and pathogenicity has not been systematically assessed across all material classes. [164][165][166][167] Hazard assessment of "P"-class 2D materials must obviously focus on the solid nanosheets themselves and may depend in complex ways on multiple properties such as lateral dimension, flexibility, and aggregation state. Because of the long-time scales potentially involved in pathogenesis, "P" materials represent the most difficult case for proper testing and hazard assessment of 2D materials.…”
Section: Materials Classification For Technology Development and Risk...mentioning
confidence: 99%